THE CULTURE OF SPEECH AMONG TEACHERS AND LEADERS: ISSUES AND SOLUTIONS - Ubaydullayeva Bakhtigul; Abdumutalibova Kibriyo (TADQIQOTLAR, 2025)
Abstract:  This  article  examines  the  significance  of  speech  culture  in  the professional activities of teachers and leaders. Effective oral communication plays a crucial role in education and management, serving not only as a means of conveying information but also as a tool for influence, motivation, and leadership. The paper explores key aspects of speech etiquette, linguistic clarity, intonation, and the use of paralinguistic  elements.  Furthermore,  the  study  highlights  the  importance  of developing communicative competence in order to ensure successful interaction and enhance  public  speaking  skills  among  professionals  in  teaching  and  leadership positions.